Challenges and strategies for gender mainstreaming policy in smart city development in Indonesia - Wahyudi, Ruslan; Elanda, Yelly (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2023)
A smart city is an urban policy innovation that can improve the community's quality of life by promoting environmental, social, and economic sustainability issues. The involvement and participation of civil society in developing smart cities is a major issue in implementing inclusive smart cities. However, gender issues are often forgotten in developing sustainable smart cities. This article examines two issues. First, the importance of gender issues integration in the development of sustainable smart cities in Indonesia. Second, the importance of gender mainstreaming policy in the development of smart cities in Indonesia. This is a desk study or literature study. Data were obtained from research results published in national and international journals. Data was obtained through accredited journal search engines, namely google scholar, SagePub and Researchgate. The research results show that development of smart city in Indonesia is not yet gender responsive, causing gender inequality gender and excluding women from development.  To respond to this, thus there is a need for gender mainstreaming policies in developing smart cities through an overview of the challenges of gender mainstreaming in developing smart cities. Thus, this research recommends a gender mainstreaming strategy as a policy in developing smart cities in Indonesia. Gender mainstreaming policy in smart city development need to be to create a smart city life that is just, inclusive and involves women in development.